Evolutionary conservation and structural localizations suggest a physical trace of metabolism's progressive geochronological emergence. Issue 12 (12th August 2020) - Pollack, J. Dennis; Gerard, David; Makhatadze, George I.; Pearl, Dennis K.
Abstract: We studied multiple sequence alignment (MSA) consensus amino acid distributional patterns in 2844 amino acid sequences of the eight enzymes of the Kreb's oxidative tricarboxylic acid pathway (oTCA) in Archaea, Bacteria and Eukarya and 5545 sequences of 33 bacteria as geochronologically separated enzymes with MSA consensus site modal identities. The 33 bacteria were 20 presumptive examples of early-oldest (Hadean-Archaean) ('Epoch I') or 13 late-newest (contemporary) ('Epoch III') appearing enzymes on Earth. The enzyme's MSA consensus sites were identified by their modal identity, % Occupancy in one of nine-graded evolutionary-conservation zones (CZs) and the Euclidean distance (Å) from each of their consensus MSA Cɑs to the same atom (Anchor-atom) in their reported functional center. These MSA consensus sites are tetrad-data points called recovered-amino acids (RAA). Across Domains, the % Occupancies of the eight-dominant RAAs of the Kreb's cycle and the 33 bacteria were found to be similarly ranked. Compared to Trifonov's 'putative ranked temporal order of the appearance of amino acids on Earth' (TOAE), the greatest statistical concordance with tetrad-RAAs across Domains were those characterized as within the most-evolutionary conserved conservation zone (CZ9), typically nearest (Å) their enzyme's catalytic/active center. The geochronologically characterized early-oldest Hadean-Archaean Bacteria 'Epoch I' enzymes, compared to late-newest Bacteria enzymes, had greater average numbers of amino acid residues/sequence and a statistically significant larger variability in their RAA compositional-Å 3 -volumes. The late-newest 'Epoch III' enzymes had statistically significant lower volumetric values, specifically, their native Å 3 -volume, void-volume and volume change on unfolding. Our enzyme data suggest a geochronological trace of ' metabolism's progressive emergence '. Communicated by Ramaswamy H. Sarma